Enhancement for automatic prayer chair from expert review requirement / Wan Nurul Ain Wan Mat Yim - Wan Mat Yim, Wan Nurul Ain (2015)
Prototype of Automatic Prayer Chair has been developed for elderly who having problem when standing while salat and also for elderly who having forgetfulness or was-was in rakaat while salat. However, the prototype of Automatic Prayer Chair lack of the expert review in terms of design to evaluate the requirement for Automatic Prayer Chair. Three objectives were developed in this project which is to identify the requirement for Automatic Prayer Chair, to evaluate the requirement for Automatic Prayer Chair and to propose enhanced requirement for Automatic Prayer Chair. Expert review methodology has been used to evaluate the requirements for Automatic Prayer Chair. Three perspective of the expert review involved, first from Islamic perspective, second ergonomic perspective and third from mechanical perspective. To reach this purpose qualitative method has been used to evaluate the requirement of Automatic Prayer Chair. The data was collected through semi-structured interview with the experts. Recommendations for improvements of the system are made based on comments highlighted by the experts during the interviews. Most experts said that size of Automatic Prayer Chair is quite large and might use large space. It also quite bulky and heavy for elderly people to carry around especially to take it to the mosque. As a solution they suggested to reduced the size and weight of the chair in terms of its material, easily folded and portable. There are two future recommendations has been listed. First to conduct focus group interview with elderly as users for Automatic Prayer Chair, so from the user perspective will give more details about their requirement and second to modify Automatic Prayer Chair prototype based on its limitations and recommendation suggested by experts.